The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3748/wjg.v22.i18.4501
|View full text |Cite
|
Sign up to set email alerts
|

miR-30b inhibits autophagy to alleviate hepatic ischemia-reperfusion injuryviadecreasing the Atg12-Atg5 conjugate

Abstract: miR-30b inhibited autophagy to alleviate hepatic ischemia-reperfusion injury via decreasing the Atg12-Atg5 conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The beneficial effect of BM-MSCs was further confirmed by Fu et al (25), who documented that the hepatoprotection provided by BM-MSCs following I/R injury was dependent on the inhibition of hepatocellular apoptosis and the stimulation of N-acetyltransferase 8 regeneration in vivo or in vitro. Consistent with these observations, the present study confirmed that BM-MSCs had beneficial effects against liver I/R injury in vivo by observing levels of ALT/AST and alterations in histomorphology that were consistent with certain published papers (41,42). Previous studies revealed that MSCs attenuated I/R injury in solid organs through various complex mechanisms, including an anti-inflammatory reaction (12,40), angiogenesis (43), anti-oxidative stress (44,45), and immunomodulation (46).…”
Section: Discussionsupporting
confidence: 91%
“…The beneficial effect of BM-MSCs was further confirmed by Fu et al (25), who documented that the hepatoprotection provided by BM-MSCs following I/R injury was dependent on the inhibition of hepatocellular apoptosis and the stimulation of N-acetyltransferase 8 regeneration in vivo or in vitro. Consistent with these observations, the present study confirmed that BM-MSCs had beneficial effects against liver I/R injury in vivo by observing levels of ALT/AST and alterations in histomorphology that were consistent with certain published papers (41,42). Previous studies revealed that MSCs attenuated I/R injury in solid organs through various complex mechanisms, including an anti-inflammatory reaction (12,40), angiogenesis (43), anti-oxidative stress (44,45), and immunomodulation (46).…”
Section: Discussionsupporting
confidence: 91%
“…AML12 cells were cultured in six well plates to 60‐70% confluence. The cells were transfected with tandem GFP‐RFP‐LC3 adenovirus (Hanbio, Shanghai, China) according to the GFP‐RFP‐LC3 instruction manual to further confrm autophagy induction …”
Section: Methodsmentioning
confidence: 99%
“…For example, miR-30b, for which a predicted target site resides in the 3ʹ-UTR of autophagy-associated gene 12 (Atg12), has been shown to modulate autophagy in hepatic ischemia-reperfusion injury [24]. The current study aimed to determine the potential role of miR-30b in TNF-α-induced apoptosis, autophagy and differentiation in the ATDC5 chondrogenic cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have indicated some novel roles for miRNAs in the regulation of autophagy [22,23]. The 3ʹ-UTR of autophagy-associated gene 12 (Atg12) was reported to contain a predicted target site for miRNA-30b (miR-30b) and this miRNA has been shown to modulate autophagy in hepatic ischemia-reperfusion injury [24].…”
Section: Introductionmentioning
confidence: 99%